The Coracoacromial Ligament: Anatomy, Function, and Clinical Significance. Issue 4 (27th April 2017) - Rothenberg, Adam; Gasbarro, Gregory; Chlebeck, Jesse; Lin, Albert
The coracoacromial ligament (CAL) was first described as a pain generator by Dr Charles Neer in the early 1970s. Since that time, considerable controversy regarding CAL management during acromioplasty has persisted. This review aims to better understand the role of the CAL in shoulder physiology and pathology. Sixty-six articles from 1958 to 2016 were identified using an electronic search of PubMed, Cochrane Library, AccessMedicine, and MD Consult for case series as well as cohort and prospective studies. The authors used "coracoacromial ligament" and "coracoacromial veil" as medical subject headings (MeSH). In addition, reference lists from all identified articles were reviewed for studies that the search terms may have omitted. The CAL plays an important role in shoulder biomechanics, joint stability, and proprioception. Morphological variance of the CAL is evident throughout the literature. Age-dependent changes due to chronic stress and cellular degradation cause thickening and stiffening of the CAL that may contribute to a spectrum of shoulder pathology from capsular tightness to rotator cuff tear arthropathy and impingement syndrome. The CAL is an integral component of the coracoacromial arch. CAL release during acromioplasty remains controversial. Future clinical outcomes research should endeavor to advance the understanding of the CAL to refine clinical and intraoperative decision making regarding its management.